FUNDAMENTAL DIFFERENCES, AS WELL AS SIMILAR FEATURES OF PART-TIME WORK AND COMBINATION OF PROFESSION (POSITIONS) - Khojabekov Muftulla Jolmurza uly (Galaxy International Interdisciplinary Research Journal, 2023)
The article discusses one of the main institutions of Labor Law, in particular, part-time work, as well as its differences from combining a profession (positions). It is noteworthy that often in practice there are cases of incorrect use of the terms “part-time work” and “combination” that are close in meaning. In order to avoid the unlawful application of the norms of labor legislation, it seems relevant to consider and identify, through a comparative legal analysis, similar and distinctive features of the indicated terms. In addition, the article also reflects the same changes in the new Labor Code of the Republic of Uzbekistan. During the study, the author studied problematic cases from practice, and proposed ways to resolve them. In addition, the criteria necessary for comparison are proposed, and proposals are made for further improvement of labor legislation.